Hospital service for ischemic stroke patients in Brazilian countryside: are we still in the ‘80s? - Junior, Antonio Fernando Ribeiro Silva; Santos, Gabriel Calasans dos; Kaneto, Carla Martins; Jesus, Pedro Antonio Pereira de; Melo, Paulo Roberto Santana de (Arquivos de Neuro-Psiquiatria, 2022)
Background Stroke is one of the most common causes of death and incapacity in the world. The benefits of reperfusion therapies and hospitalization in neurologic intensive care units (ICUs) are undeniable. However, these treatments are not widely available in a continental-sized country like Brazil.Objective To describe the treatment for ischemic stroke and the functional outcome 90 days after the hospitalization of patients in the Brazilian countryside.Methods Observational, prospective case series study design. The data collected refer to randomly selected patients hospitalized in 3 hospitals in the south region of the state of Bahia between December 2018 and December 2019.Results The population consisted of 61 consecutive patients. They were elderly (median age: 62 years old); with a predominance of hypertension (82%); and were light to moderate stroke cases (National Institute of Health Stroke Scale [NIHSS] median: 7). A total of 37.7% of the cases arrived at the hospital in a < 4.5-hour window but received no reperfusion therapy. Of these, 94.3% were discharged from the hospital with a prescription for antiplatelets or anticoagulant. A total of 64.1% of the patients received a statin prescription. At the end of the follow-up period, the general mortality was 21%. Almost half of the population (47.9%) evolved to an unfavored outcome (modified Rankin scale [mRs]: 3 to 6).Conclusion Our population presented sociodemographic and comorbidities characteristics similar to those of other national samples. No reperfusion therapy was used and the treatment was basically secondary and prophylaxis-oriented, and almost half of the population evolved with incapacities and a high mortality rate, despite the initial low clinical gravity.
Keywords: Stroke; Risk Factors; Hospitalization; Prognosis